2017
DOI: 10.1080/10496491.2018.1405523
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Attitudes and Behavioral Intentions Toward In-app Mobile Advertisements

Abstract: Mobile apps show a heavy usage pattern and compelling growth figures. This study seeks to examine consumers' attitudes toward in-mobile advertisements in terms of mobile advertising value. The samples are from the United Kingdom (UK) and India because the nationals of these countries exhibit a high degree of dissimilarity in a number of Hofstede's cultural dimensions. The findings suggest that factors such as perceived entertainment, credibility and information significantly improve attitudes toward in-app adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 45 publications
5
46
1
2
Order By: Relevance
“…More and more consumers are carrying smartphones, which increasingly receive compelling offers that instantaneously pop up on their screens. Mobile advertising alerts allow marketers to deliver ads and coupons through branded mobile apps customised to individual consumers' preferences, geographic location and the time of day; this increases the impact of in-app advertising [75]. Ref.…”
Section: Effects Of Mobile Advertising Alert Content On Attitudementioning
confidence: 99%
“…More and more consumers are carrying smartphones, which increasingly receive compelling offers that instantaneously pop up on their screens. Mobile advertising alerts allow marketers to deliver ads and coupons through branded mobile apps customised to individual consumers' preferences, geographic location and the time of day; this increases the impact of in-app advertising [75]. Ref.…”
Section: Effects Of Mobile Advertising Alert Content On Attitudementioning
confidence: 99%
“…Other researchers posited that credibility has a positive relationship with advertising value (Liu et al, 2012), and attitudes towards online, traditional and mobile advertisements (Xu, 2006). Sigurdsson et al, (2017) found that credibility is related to attitudes in advanced countries but not necessarily in emerging countries. Trust is closer to credibility and is one the most important components worth considering in mobile marketing.…”
Section: Credibilitymentioning
confidence: 97%
“…Keinformatifan dapat meningkatkan pengetahuan dan pemahaman serta memuaskan kebutuhan kognitif konsumen akan informasi produk atau layanan yang diberikan. Kualitas informasi telah terbukti berdampak besar terhadap estimasi jumlah konsumen yang berpengaruh nyata pada kepercayaan konsumen terhadap suatu perusahaan (Sigurdsson et al 2018). Informasi juga didefinisikan sebagai suatu instrumen yang dapat membantu konsumen memahami suatu produk yang bersifat persuasif sehingga konsumen dapat dengan mudah menggunakan produk tersebut (Hendraningtiyas & Soediono, 2015).…”
Section: Pendahuluanunclassified
“…38.64% responden laki-laki menyatakan persetujuannya bahwa kelengkapan fitur informasi pada aplikasi Go-Food lebih baik (skor rata-rata 4.06). Dari hasil tersebut dapat dikatakan bahwa persepsi keinformatifan dapat meningkatkan pengetahuan serta memuaskan kebutuhan kognitif konsumen akan informasi produk atau layanan yang diberikan (Sigurdsson et al 2018).…”
unclassified